Manajemen Pembelajaran Bahasa Arab Pada Madrasah Ibtidaiyah: Konstruk Kurikulum Merdeka Berbasis Komunitas - Machmuddin, Rosbiah; Yahya, M.; Rusydi, Muhammad (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
This article is a literature review that focuses on examining the management of Arabic language learning in madrasah ibtidaiyah in the community-based independent curriculum. The results of the study show that the management of Arabic language learning in madrasah ibtidaiyah in the community-based independent curriculum is built on three stages, namely planning, implementation, and evaluation of Arabic language learning. At the planning stage, the preparation of the Madrasah Operational Curriculum (KOM), the preparation of Learning Objectives (TP) and the Flow of Learning Objectives (ATP), the preparation of teaching modules, was carried out. At the implementation stage, difference learning and P5-PPRA design (Pancasila Student Profile Strengthening Project and Rahmatan Lil Alamin Student Profile) were carried out. As for the evaluation stage, formative and summative evaluations need to be carried out to ensure that all Arabic learning processes are in the right flow in terms of planning and implementation as a stage, in which the evaluation is an evaluation as a stage of management of Arabic learning at madrasah ibtidaiyah in an independent community-based curriculum